High-solid and Multi-phase Bioprocess Engineering Theory and Practice - Chen, Hongzhang (Green Chemistry and Sustainable Technology,, 2018)
This book provides a comprehensive description of theories and applications of high-solid and multi-phase bioprocess engineering, which is considered as an important way to address the challenges of "high energy consumption, high pollution and high emissions" in bio-industry. It starts from specifying the solid-phase matrix properties that contribute to a series of "solid effects" on bioprocess, including mass transfer restrictions in porous media, water binding effects, rheological changes. Then it proposes the new principles of periodic intensification which combines the normal force and physiologic characteristics of microorganism for the bioprocess optimization and scale-up. Further breakthroughs in key periodic intensification techniques such as periodic peristalsis and gas pressure pulsation are described in detail which provide an industrialization platform and lay the foundation for high-solid and multi-phase bioprocess engineering. This book offers an excellent reference and guide for scientists and engineers engaged in the research on both the theoretical and practical aspects of high-solid and multi-phase bioprocess.